A Analysis of experiments on the process of deodorization of vegetable oil using floating nozzles: Analysis of experiments on the process of deodorization of vegetable oil using floating nozzles - Sultanov, Sardor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In short , experiments have shown the effectiveness of a floating wooden nozzle device compered to exiting deodorizers. As a result of processing cottonseed oil in a new periodic device, various volatile components in the finished oil were reduced in a short time, which led to an improvement in the quality od the oil is coming. Based on the experiments conducted proposed facility, proposals for industrial construction were developed